Building Competitive Advantage in the Indonesian Logistics Sector: the Combined Impact of Service Quality, Marketing, and Supply Chain Flexibility on Firm Performance - Ardian Tri Bawono; Sri Widyastuti; Derriawan (CV Edujavare Publishing, 2026)
The logistics industry in Indonesia faces increasing pressure to balance operational efficiency with market responsiveness amid intense competition and geographical complexity. This study aims to systematically synthesize empirical evidence regarding the influence of Marketing-Oriented Logistics Service Quality (MOLSQ), Marketing Capability (MC), and Supply Chain Flexibility (SCF) on logistics firm performance through the mediating role of competitive advantage. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Twenty-five empirical studies published between 2020 and 2025 were selected from Scopus, ScienceDirect, Google Scholar, and nationally accredited SINTA journals. The synthesis indicates that MOLSQ, MC, and SCF consistently exert positive effects on competitive advantage, which subsequently enhances logistics firm performance. The findings further demonstrate that competitive advantage serves as the principal mechanism through which these strategic capabilities generate superior organizational outcomes. This review extends the Resource-Based View and Dynamic Capabilities Theory by proposing an integrated conceptual framework that combines logistics service quality, marketing capability, and supply chain flexibility within the Indonesian logistics context. The study also provides practical insights for logistics managers seeking to strengthen competitiveness through integrated strategic capabilities.